Konflik pengelolaan logam berat dalam sistem pertanian berkelanjutan: Pemanfaatan kitosan cangkang kerang sebagai flokulan berteknologi elektrokoagulasi, absorpsi, dan filtrasi - Akhyar Arista Widya; Desynia Widyasari; Eddi Prayitno (Institute for Advanced Science Social, and Sustainable Future, 2024)
Background: Water plays a central role in sustaining human life and ecosystems on Earth. It is used in various aspects of daily life, including consumption, agriculture, and industry. However, current environmental issues indicate that we are experiencing severe disruptions in water ecosystems, especially concerning water pollution. To address this problem, the proposed solution is to implement the principles of electrocoagulation, adsorption, and filtration to recycle wastewater from the tofu industry and mitigate serious water pollution issues. Methods: This study is an experiment testing electrocoagulation, adsorption, and filtration devices, as well as the effectiveness of green mussel shell chitosan as an adsorbent. The study will be conducted in Boyolali for two months, using chili plants and Nile tilapia as samples. The samples will be given three treatments: wastewater, recycled water, and well water (control). The research procedure includes device fabrication, testing, and evaluation. Data will be analyzed through pH, temperature, DO, TAN, metal content in water, plant growth, and Nile tilapia survival rate tests. Findings: Electrocoagulation as the initial stage of wastewater treatment aims to precipitate solid particles through redox reactions, while the adsorption stage using chitosan from green mussels is designed to effectively filter toxic metal ions. Subsequently, advanced filtration is performed to enhance filtering efficiency. In addition to environmental benefits, this innovation also offers economic potential through the use of green mussels to produce chitosan. Chitosan, with its cationic properties, non-toxic biological profile, and chemical reactivity, makes it an ideal adsorption agent. The management of this solution involves four main stages: 1) Planning stage (Plan); 2) Implementation stage; 3) Control stage (Check); 4) Action stage; Implementation. Conclusion: The recycled wastewater from tofu production is expected to support sustainable agriculture, serving as a substitute for main water sources, especially during the dry season. Novelty/Originality of this article: This research explores a sustainable solution for water pollution using electrocoagulation, adsorption, and filtration with green mussel shell chitosan, leveraging the economic potential of green mussels, and applying recycled water to agriculture and aquaculture.